PERBAIKAN TATA LETAK FASILITAS DENGAN METODE SYSTEMATIC LAYOUT PLANNING (SLP) UNTUK MENGURANGI JARAK PERPINDAHAN MATERIAL (STUDI KASUS UKM KERUPUK KAROMAH) - Bayu Saputra; Zaenal ARifin, ST, MT; Abdullah Merjani (PROFISIENSI : Jurnal Program Studi Teknik Industri, 2020)
This study aims to improve the layout of facilities to reduce the distance of material transfer in Karomah Crackers SMEs by using the Systematic Layout Planning (SLP) method in which the procedure consists of three stages, the analysis phase covering the material flow analysis Activity Relationship Chart (ARC) analysis, Activity Analysis Relationship Diagram (ARD), analysis of the needs of the area and available area. The adjustment phase includes the planning of room relationship diagrams and alternative layout plans. The evaluation stage was carried out by selecting alternative layout designs. Based on the Systematic Layout Planning (SLP) method, 3 proposal layouts were produced, all of which had minimized the distance. Layout I can save a distance of 11%. Proposed Layout II saves a distance of 35% and the proposed layout III can save a distance of 30%. So that the layout of proposal I is recommended as a chosen proposal layout.